2019
DOI: 10.1186/s40359-019-0298-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its associated sociodemographic factors among Iranian female adolescents in secondary schools

Abstract: Background Across the globe, depression is a common psychiatric disorder and is the main cause of disability among adolescents. To this end, this study was conducted to screen for the prevalence of depression among secondary school female students in the city of Hamadan, in western Iran. Methods In this cross-sectional study, a total of 670 secondary school female students, within the age range of 15–18 years were investigated using multistage random sampling method. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 41 publications
10
40
3
3
Order By: Relevance
“…Our results showed that the association between depressive symptoms and suicidal ideation was stronger in adolescents with a low socioeconomic status. These findings, in line with previous research [ 39 , 40 , 41 ], indicate that a low family socioeconomic status may be a risk factor for the emergence and maintenance of some internalizing problems. These results may help us to identify vulnerable populations and evidence the convenience of developing primary prevention programs designed to target non-referred adolescents who come from economically disadvantaged family contexts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that the association between depressive symptoms and suicidal ideation was stronger in adolescents with a low socioeconomic status. These findings, in line with previous research [ 39 , 40 , 41 ], indicate that a low family socioeconomic status may be a risk factor for the emergence and maintenance of some internalizing problems. These results may help us to identify vulnerable populations and evidence the convenience of developing primary prevention programs designed to target non-referred adolescents who come from economically disadvantaged family contexts.…”
Section: Discussionsupporting
confidence: 92%
“…Another interesting finding is that when both socioeconomic status and parents’ educational level were considered in the same analysis, suicidal ideation was significantly associated with socioeconomic status, but not with parents’ educational level. As predicted, and consistent with available evidence [ 40 , 41 ], we found higher levels of suicidal ideation among referred and non-referred adolescents from families with a low socioeconomic status. In contrast, the relationship between socioeconomic status and depressive symptoms was not significant when parents’ educational level was partialled out.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The internal behavior of girls, the way in which they respond to stress, the effect of the adolescence stage, and the effect of cultural discrimination could be possible causes of higher depression rates among females compared to males. Moeini et al [34] reported that in the puberty stage, there are various possible psychological risk factors that lead to depression, particularly among girls. Schimelpfening [35] reported that the social and socialization role of females, gender differences, coping mechanisms, stressful life events, and hormonal changes in females were found to be risk factors of depression.…”
Section: Discussionmentioning
confidence: 99%
“…By the sample size calculation formula for a crosssectional [24], at Z α/2 = 1.96, α = 0.05, p = 0.52 [25], and considering a 20.0% nonresponse rate, then at least 459 samples were required for the analysis. The five study districts were selected purposively, and the CCHs in the selected districts were selected by a simple random method.…”
Section: Sample Size Calculation and Sampling Techniquementioning
confidence: 99%